Application of comprehensive nursing in the treatment of chronic constipation with fecal microbiota transplantation (综合护理在粪菌移植治疗慢性便秘中的应用) - WANG Xuedan (王雪丹); ZHANG Yong (张勇) (中西医结合护理)
Objective To observe and analyze the clinical effect of comprehensive nursing interventions in the treatment of chronic constipation with fecal microbiota transplantation. Methods In this study, 46 patients with chronic constipation who received fecal microbiota transplantation were selected as the research object, and were randomly divided into observation group and control group, with 23 cases in each group. The observation group was given comprehensive nursing interventions during the treatment, while the control group was given routine nursing. The nursing effect was evaluated by comparing and analyzing the Knowles-Eccersley-Scott Symptom Questionnaire (KESS), Patient Assessment of Constipation Quality of Life(PAC-QOL) score and satisfaction of the two groups. Results After treatment, KESS score of observation group was significantly lower than that of control group, with a significant difference(P＜0. 05). The PAC-QoL score in the observation group was significantly lower than that in the control group, with a significant difference(P＜0. 01). The satisfaction rate of the observation group was higher than that of the control group with a significant difference(P＜0. 05). Conclusion The application of comprehensive nursing interventions in the treatment of chronic constipation by fecal microbiota transplantation can improve the therapeutic effect, improve patient’s quality of life and satisfaction. (目的 观察综合护理干预在粪菌移植治疗慢性便秘患者中的应用效果。方法 选取2019年4月—2021年10月医院收治的接受粪菌移植的46例慢性便秘患者为研究对象, 随机分为观察组与对照组, 各23例。对照组给予常规护理, 观察组接受综合护理干预。比较分析2组Knowles-Eccersley-Scott症状评分(KESS)和便秘患者生活质量量表(PAC-QoL), 评价患者满意度。结果 干预后, 观察组患者KESS评分低于对照组, 差异有统计学意义(P＜0. 05); 观察组患者PAC-Qol评分低于对照组, 差异有统计学意义(P＜0. 01); 观察组满意度评价高于对照组, 差异有统计学意义(P＜0. 05)。结论 在粪菌移植治疗慢性便秘过程中开展综合护理干预, 能提高治疗效果, 改善患者生活质量, 提高满意度。)